As influências afetivas no ensino e aprendizagem de matemática - Cardoso, Evelyn Rosana (2010)
The importance on the emotional stance within the school environment in the Mathematics class is provided. Current research reports manifestations of emotions in students of the fifth grade of the primary school in the context of their responses to an open questionnaire and during a half-structured recorded interview so that possible consequences in learning could be detected. Nine students of the fifth grade of a government school in the state of Paraná, Brazil, were the subjects of current research. Whereas students manifested their feelings with regard to Mathematics and the Math teachers, the latter were thought to be differentiated people. Facility or difficulty in deal with Mathematics was related to intellectual capacity which was defined by some as "mart intelligence." The participants also desired that the teacher gave more individual attention to students who failed to understand the lesson thoroughly.